Can Joy Buy You Money? The Impact of the Strength, Duration, and Phases of an Entrepreneur’s Peak Displayed Joy on Funding Performance - Jiang, Lin; Yin, Dezhi; Liu, Dong (Academy of Management Journal, 2019)
Does displaying positive emotions (e.g., joy) during a funding pitch help an entrepreneur gain more financial support? Past research has approached this question mostly by treating emotional displays as static and focusing on the overall or average levels of displayed emotions. However, emotional displays are temporally dynamic and more salient in some moments or phases than others. Drawing from gestalt characteristics and event system theories, we take a dynamic approach to examine the “peak” moments of entrepreneurs’ displayed joy—specifically, the strength and duration of peak displayed joy during different phases of a pitch. We analyzed data from over eight million frames in 1,460 pitch videos, using the latest facial expression analysis technology. The findings unveil the benefit of pitching with a greater level of peak displayed joy, especially during the beginning and ending phases of a pitch. Moreover, the amount of time an entrepreneur spends at the peak level of his or her displayed joy has an inverted U-shaped relationship with funding performance. This research highlights not only the importance of investigating emotion temporal dynamics in the interpersonal context, but also the unique research opportunities provided by facial expression analyses in understanding complex management phenomena.